(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
Reading in English for Specific Purposes (ESP) is a complex and interactive activity that requires significant time and resources to cultivate. The process of reading comprehension involves deriving meaning from a text and actively engaging with its content. This article presents a theoretical framework that addresses the classification of reading skills, criteria for ranking and transferring skills, and explores the impact of the balance between skills and language on the teaching of reading in ESP. It emphasizes the importance of adopting diverse reading styles, strategies, and techniques in the second/foreign language classroom to facilitate successful interaction with authentic ESP texts and enhance second language readers’ efficiency. The article also examines various techniques for testing reading comprehension. Additionally, it investigates the factors influencing success in reading comprehension tasks, including the type and duration of students’ training, the length of their English study at the faculty, the duration of training in reading skills, the frequency of testing, and the nature of texts used for reading comprehension assessments.